Governance of dominant companies in the agro coffee chain: The case of the region Turrialba, Costa Rica - Cordero Peñaranda, Rosa Elena (2015)
The governance conducted by the parties involved in the coffee chain in the region of Turrialba, Costa Rica, is analyzed in this paper. Governance is exercised differently by the various parties in the chain. For instance, coffee mills exercise power over farmers given that the former establishes coffee quality and safety conditions. The most rigid power structure is from transnational roasting companies, which set coffee quality standards for marketing and, in most cases, set coffee prices.